Semi-rigid behaviour of connections in precast concrete structures - Görgün, Halil (1997)
Multi-storey precast concrete skeletal structures are assembled from individual prefabricated components which are erected on-site using various types of connections. In the current design of these structures, beam-to-column connections are assumed to be pin jointed. This current research work focuses on the flexural behaviour of the beam-to-column connections and their effect on the behaviour of the global precast concrete frame.